Perancangan Alat Hydrocracking Untuk Pembuatan Pabrik Base Oil dan Gasoline Dari Limbah Plastik - Huda, Istaniyah; Abrina Anggraini , Sinar Perbawani; Ma'sum, Zuhdi (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
The need for lubricants in Indonesia for industrial machines, motor vehicles, shipping, heavy equipment, agricultural machines, mining and various other machine lubricants is being used in increasing quantities. Through a pyrolysis process followed by a hydrocracking process, plastic waste can be processed into base oil as the main product and gasoline as a side product. Plastic waste raw materials can be processed using a hydrocracking reactor to produce products in the form of Synthetic Base Oil and gasoline with a conversion of up to 90%, so it is necessary to design a factory for the production of base oil with a capacity of 35,000 tons/year and gasoline with a capacity of 27,000 tons/year using Hydrocracking Reactor. The aim of this research is to determine the design dimensions of a Hydrocracking Reactor with a capacity of 194,444.44 kg/day for making base oil and gasoline from plastic waste (PE). From the mass and heat balance calculations, the equipment specifications are obtained in the form of a Hydrocraking Reactor with a single stage type, a mass flow rate of 54,665.36 kg/hour, a tank diameter of 27.5 ft and a height of 30 ft made from SA-240 Grade A stainless steel which is capable of processing feed. enters from the pyrolysis reactor with batch operating conditions (every 1.5 hours). The head thickness is 0.4 in, the shell thickness is 0.35 in, and the setting area is 510.25 ft2.